AIM2 Inflammasome Activation Leads to IL-1α and TGF-β Release From Exacerbated Chronic Obstructive Pulmonary Disease-Derived Peripheral Blood Mononuclear Cells - Colarusso, Chiara; Terlizzi, Michela; Molino, Antonio; Imitazione, Pasquale; Somma, Pasquale; Rega, Roberto; Saccomanno, Antonello; Aquino, Rita P.; Pinto, Aldo; Sorrentino, Rosalinda (Frontiers in Pharmacology, 2019)
Chronic obstructive pulmonary disease (COPD) is now the fourth-leading cause of death worldwide and its prevalence is increasing. The progressive decline of lung function and airway remodelling are a consequence of chronic inflammatory responses. It was recently postulated the involvement of the inflammasome in COPD, although the underlying mechanism/s still need to be elucidated. Therefore, we isolated peripheral blood mononuclear cells (PBMCs) from exacerbated/unstable COPD patients. The stimulation of PBMCs with an AIM2 inflammasome activator, Poly dA:dT, led to IL-1α, but not IL-1β, release. The release of this cytokine was caspase-1- and caspase-4-dependent and correlated to higher levels of 8-OH-dG in COPD compared to non-smoker and smoker-derived PBMCs. Interestingly, AIM2-depedent IL-1α release was responsible for higher TGF-β levels, crucial mediator during pro-fibrotic processes associated to COPD progression. In conclusion, our data highlight the involvement of AIM2/caspase-1/caspase-4 in IL-1α-induced TGF-β release in unstable COPD-derived PBMCs, opening new therapeutic perspectives for unstable COPD patients.